Nicotine dependence comparison of dual use of cigarettes and e-cigarettes among Malaysian university students - Elsaieh, Afaf Masaud; Shohaimi, Shamarina; Mohd Nadzir, Mohd Noor Hisham; Mohd Puad, Mohd Hazwan (Society for Science and Education, 2023)
The increasing prevalence of dual cigarette use (traditional cigarettes and e-cigarettes) among higher education students in Malaysia raised concerns about potential health risks associated with this habit. This study aims to investigate the differences in nicotine dependence and smoking habits between single and dual cigarette users. A cross-sectional survey was conducted among 224 students from four higher education institutions in the Klang Valley. Data were collected using self-administered questionnaires, which included questions on personal information, nicotine dependency, and smoking habits. The Mann-Whitney Test was used to test the hypotheses. The findings indicated no significant difference in nicotine dependence and smoking habits between single and dual cigarette users. However, the study highlighted the potential health risks associated with dual cigarette use. The results emphasize the need for policymakers to implement stricter smoking regulations in higher education facilities and increase student awareness of the dangers of smoking. Further research should focus on understanding the reasons for dual cigarette use and developing targeted interventions to address this public health issue.